2018
DOI: 10.1097/igc.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cancer Is Associated With Dissatisfaction With Care—A Longitudinal Analysis Among Ovarian and Endometrial Cancer Patients

Abstract: After diagnosis of recurrent disease, endometrial and ovarian cancer patients were less satisfied with care compared with patients without a recurrence. Our findings suggest that patients with recurrent cancer are in need of care that is better tailored to their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Selecting only disease-free patients may have reinforced this influence. Generally, patients without recurrence are more satisfied with care than patients with recurrence [18]. In addition, we did not have details on the patient's persistent symptoms, which may be influencing preference as well.…”
Section: Discussionmentioning
confidence: 98%
“…Selecting only disease-free patients may have reinforced this influence. Generally, patients without recurrence are more satisfied with care than patients with recurrence [18]. In addition, we did not have details on the patient's persistent symptoms, which may be influencing preference as well.…”
Section: Discussionmentioning
confidence: 98%
“…H41021924) via intravenous injection; 30 mg of cimetidine (specification: 0.2 g; manufacturer: Guangzhou Baiyunshan Mingxing Pharmaceutical Co. Ltd.; SFDA approval No: H44024199) via intramuscular injection, and 40 mg of diphenhydramine (specification: 20 mg; manufacturer: Beijing Yookon Pharmaceutical Co. Ltd; SFDA approval no. H11020523) via intramuscular injection, in order to prevent adverse reactions [11]. Patients in the combination group were given Yiqi Jianpi Yangxue Decoction obtained from 30 g of Astragalus membranaceus, 20 g of poria cocos, 15 g of oldenlandia, 10 g of curcuma zedoary, 10 g of dangshen, 10 g of kuh-seng, 10 g of ginger, 10 g of bighead atractylodes rhizome, 10 g of Paeonia lactiflora, 8 g of rhizoma sparganii and 8 g of monkshood.…”
Section: Treatmentsmentioning
confidence: 99%
“…Patients in the SCP arm experienced more symptoms, were more concerned about their illness, and were more emotionally affected than patients in the usual care arm [17]. Further analyses showed increases in health care use among women with anxiety symptoms and those who received radiotherapy [18,19]. Investigators found that patients with ovarian cancer who had lower trust that the treatment would cure their disease due to the SCP reported worse emotional functioning 6 months after treatment [20].…”
Section: Introductionmentioning
confidence: 99%